Eksistensi Televisi Swasta di Era Konvergensi Media - Vizcardine Audinovic (LPPM Stikosa - AWS, 2021)
The presence of new media has indeed threatened the existence of television as a means of entertainment and a source of public information coupled with the pandemic outbreak. The speed and different technology offered by new media have made people start to switch to consuming new media such as YouTube and social media. Therefore, television must try to adjust the existing technological developments so that the audience does not abandon it. This paper aims to determine the television strategy in facing the era of media convergence. The method used is systematic literature review of several articles by summarizing various relevant research results. The results of this paper are television is still watched by many people, it is just that the viewing pattern has changed, it is no longer communal but more individual through smartphones so that what appears is a decreased television rating. Therefore, television uses a number of ways to be able to compete with new media, including merging with other media companies, using social media, and monetizing content that is connected to other platforms. From this it can be seen that the audience will not leave television behind as long as it is able to display updated content and spread across various platforms so that it can be watched anytime and anywhere. In addition, television has the advantage of being regulated by the government so that broadcasts on television are more controlled than new media.